Technological Approaches for Novel Applications in Dairy Processing - Koca, Nurcan (IntechOpen, 2018)
Technological innovations, customer expectations, and economical situations have been forcing the dairy industry to adapt to changes in technologies and products. The goal of this book is to present some new approaches on dairy processing. It will provide several applications on the use of some novel technologies in various dairy products, the improvement of functionalities and quality systems of dairy products, and the advances in dairy wastewater treatment. The book will be useful for both practicing professionals and researchers in the dairy field. I would like to send my sincere thanks to all the authors for their hard work and contributions.